Bivalve Diversity Associated with Seagrasses in The Southern Coastal Waters of Central Lombok - Lalu M. Faatih Basmalah; Abdul Syukur; Khairuddin Khairuddin (Jurnal Biologi Tropis, 2022)
Bivalves have an important role for the aquatic environment, namely as bioindicators of environmental health and water quality associated with seagrass. Bivalves are a class of molluscs associated with seagrass. This study aims to analyze the diversity of bivalves, and the relationship of environmental factors to the habitat of bivalves. The method used in this research is the line transect and quadratic method. The research approach was through observation, data collection for seagrass and bivalves using quadrant and transect methods. Data analysis used descriptive statistical analysis, ANOVA, and Pearson correlation. The results of the study found 16 species belonging to 7 families (Veneroidae, Arcidae, Cardidae, Tellinidae, Pinnadae and Pteriidae). The highest bivalves diversity index (H') was found at Kuta Mandalika Beach at 2.40 and the lowest at Gerupuk Beach at 2.02. The ANOVA results showed that the richness and abundance of seagrass-associated bivalves in the study area was determined by the environmental characteristics of the seagrass, especially the substrate. Second, seagrass can be a suitable substrate for bivalves to survive. The results of this study can be a reference for future researchers and a source of information for study purposes and for the development of science, especially in the field of invertebrate zoology.